Analisis Pengaruh CAR, ROA, NPF, dan FDR terhadap Pembiayaan Mudharabah Bank Umum Syariah di Indonesia Tahun 2011-2020 - Salsabilla Shauma; Eni Setyowati; Imron Rosyadi (Universitas Batanghari Jambi, 2022)
Mudharabah financing is a profit-sharing-based business contract, where one party contributes capital and the other party runs a business venture (capital manager). This study aims to determine how big the influence of CAR, ROA, NPF, and FDR on Mudharabah Financing of Islamic Commercial Banks in Indonesia, with the data that has been presented. This study aims to use quantitative methods and in the form of sample data techniques, namely the Purposive Sampling technique to obtain 5 Islamic Commercial Banks (BUS). The results of this data processing show that NPF (Non Performing Finance) with a result of 0.0328 <0.1, has a significant negative effect on Mudharabah Financing. The results of the CAR (Capital Adequacy Ratio) data of 0.4530 > 0.1 have no significant effect on Mudharabah Financing at Indonesian Sharia Commercial Banks. The results of the ROA (Return On Assets) data of 0.6400 > 0.1, have no significant effect on Mudharabah Financing at Indonesian Islamic Commercial Banks. The results of FDR data (Financing to Deposit Ratio) of 0.2791 > 0.1 have no significant effect on Mudharabah Financing at Indonesian Islamic Commercial Banks.